Complications after low-velocity ballistic femur fractures: a series of 104 patients at a level 1 trauma center - Brianna R. Fram, MD; Nainisha Chintalapudi, MD; Jana Davis, MD; Ziqing Yu, MS; Rachel B. Seymour, PhD; Madhav A. Karunakar, MD; Evidence-Based Musculoskeletal Injury and Trauma Collective; Joseph R. Hsu, MD; Laurence Kempton, MD; Kevin Phelps, MD; Stephen Sims, MD; Suman Medda, MD; et al. (OTA International)
Abstract. Objectives:. To report outcomes and risk factors of complications following low-velocity ballistic fractures of the femur. Design:. Retrospective case series. Setting:. Academic Level I trauma center. Patients/Participants:. Retrospective series of 104 patients aged 18+ years presenting with low-velocity civilian ballistic femur fractures from 2011 to 2020 (OTA/AO types 31–33). Intervention:. Treatment following ballistic femur fracture. Main Outcome Measurements:. All cause complications. Results:. Our cohort experienced a 39% complication rate and 19% reoperation rate, including 3 deep surgical site infections, 15 hardware failures, and 12 nonunions. All-cause complications did not differ significantly between OTA/AO or Gustilo classifications (P = 0.56, P = 0.94). Skin and muscle management, arterial injury, amount of contamination, or muscle loss did not differ significantly between those with and without complication. Factors not associated with increased complications included time to initial antibiotics, time from injury, operative time, duration of prophylactic antibiotics, and hospital length of stay. However, all of these factors were based on our typical clinical care routine within the standard of care and were not purposefully varied. Conclusions:. We did not find any modifiable or nonmodifiable factors that increased risk of complication in our sample. We found that time to prophylactic antibiotics or time to operative debridement was within quality standards and was not associated with increased risk of complications. Our complication rate was similar to previous reports. While we found lower rates of vascular complications than previous reports and 0 cases of compartment syndrome, complication rates in our sample were driven by nonunion and implant failure. These continue to be challenging injuries with high rates of complications. Level of Evidence:. IV.